2015
DOI: 10.1093/cercor/bhv267
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Influences of Language Delay and/or Familial Risk for Dyslexia on Brain Structure in 5-Year-Olds

Abstract: Early language delay has often been associated with atypical language/literacy development. Neuroimaging studies further indicate functional disruptions during language and print processing in school-age children with a retrospective report of early language delay. Behavioral data of 114 5-year-olds with a retrospective report of early language delay in infancy (N = 34) and those without (N = 80) and with a familial risk for dyslexia and those without are presented. Behaviorally, children with a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 117 publications
4
28
0
Order By: Relevance
“…A consequent analysis of the same group of children (with a few additional subjects), examined the interaction between FHD status and a retrospective report of delay in language production . Results revealed that FHD+ children with language delay had significantly more pronounced reductions in the regions reported above; namely, occipoto‐temporal and temporo‐parietal regions.…”
Section: Early Brain Characteristics In At‐risk Children: Evidence Frmentioning
confidence: 98%
“…A consequent analysis of the same group of children (with a few additional subjects), examined the interaction between FHD status and a retrospective report of delay in language production . Results revealed that FHD+ children with language delay had significantly more pronounced reductions in the regions reported above; namely, occipoto‐temporal and temporo‐parietal regions.…”
Section: Early Brain Characteristics In At‐risk Children: Evidence Frmentioning
confidence: 98%
“…Studies examining infants and pre-reading children with a hereditary risk for dyslexia have identified atypical language development in these children, as they tend to show poor categorical speech perception, delayed onset of talking, shorter mean length of utterances, lower complexity of syllables produced, and poor receptive or expressive vocabulary [8991]. Longitudinal studies have further demonstrated the importance of these early language skills for the development of reading.…”
Section: Perceptual and Cognitive Deficits And Risk Factors Of Dyslexiamentioning
confidence: 99%
“…Longitudinal studies have further demonstrated the importance of these early language skills for the development of reading. However, these symptoms have also been observed in children with a subsequent diagnosis of specific language impairment or speech sound disorders, and could be a consequence of the high occurrence of comorbidities between dyslexia and language disorders [9194]. Therefore, delayed language development in some children with dyslexia risk is likely indicative of a cumulative contribution of etiological factors for each disorder, rather than being a specific marker of dyslexia risk.…”
Section: Perceptual and Cognitive Deficits And Risk Factors Of Dyslexiamentioning
confidence: 99%
“…These results might be related with the inter-disciplinary nature of the concept of learning disability. Disciplines of neurosciences have important implications for learning disability because it is known that learning disability is associated with some abnormalities in brain structure (Raschle, Becker, Smith, Fehlbaum, Wang & Gaab, 2015). Psychology, education and related disciplines are also important research areas in learning disability because it is also known that learning disability is characterized with abnormalities in cognitive functioning and inabilities in gaining academic skills (Hen & Goroshit, 2014;Grünke & Morrison Cavendish, 2016;Torgesen, 1999).…”
Section: Discussionmentioning
confidence: 99%